The accessibility and utilization of health services for pregnant women in selected resettlement areas in Iloilo City. - Jocsing, Mary Bernadette O.
This study was conducted to find out to accessibility and utilization of health services for the pregnant women in the resettlement areas. It aims to identify and describe the health services offered by the government. To describe the practices and problems faced by mothers in availing the health services, to identify the initiatives made by the government to ensure that the health services were delivered in the resettlement areas and to identify the expectations of the mothers from the government in the delivery of health services.